Antibacterial and anti-adherence effect of Laportea interupta ethanolic extract on Streptococcus mutans biofilm - Hutomo, Suryani; Larope, Ceny Gloria; Putri, Denise Utami; Sooai, Christiane Marlene; Kristiyanto, Haryo Dimasto (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Due to its capacity to generate extracellular polymeric substances that aid in biofilm creation, Streptococcus mutans is a leading cause of dental caries. Natural remedies, including traditional plant extracts, are being explored for their antimicrobial potential. Laportea interupta (L. interupta), known as jelatang in Indonesia, is alleged to possess a bacteria-inhibiting effect. Purpose: The purpose of this study is to evaluate the potential use of L. interupta leaf ethanolic extract to inhibit S. mutans proliferation and adherence to hydroxyapatite (HA) discs, simulating the tooth surface. Methods: The broth microdilution approach was utilized to evaluate the minimum concentration of the extract that inhibits bacterial growth. For anti-adherence assessment, HA discs pre-coated with saliva were exposed to different extract concentrations and incubated with S. mutans. Bacterial adhesion was visualized using 0.1% crystal violet staining, quantified spectrophotometrically at 595 nm, and further verified using scanning electron microscopy (SEM). Results: The extract showed inhibitory effects on S. mutans growth at 7,500 μg/ml (MIC). Anti-adherence activity was optimal at 1,500 μg/ml, and SEM analysis confirmed a reduced biofilm formation on extract-treated samples. Conclusion: Laportea interupta ethanolic leaf extract demonstrated both antibacterial and anti-adherence effects against S. mutans, suggesting its potential as a natural anti-biofilm agent for oral health applications.